PROBLEMATIKA PENGATURAN CYBERSTALKING (PENGUNTITAN DI DUNIA MAYA) DENGAN MENGGUNAKAN ANNONYMOUS ACCOUNT PADA SOSIAL MEDIA - Rahel Octora (Dialogia Iuridica, 2019)
The internet is a new world where humans interact, without limitation of distance and time. In the real world, as legal subjects, everyone must have a clear identity, proof of identification, so that the state can recognize it and the law can be upheld against it, as well as the law can protect their rights. Social media which is currently developing, allows everyone to appear and interact in cyberspace either by showing their true identity, or by using fake identities, or even interacting without identity (annonymous). Easily each person can create more than one e-mail account, which can be used to create more than one social media account. Although the creation of e-mail and social media accounts is through the cell phone number verification stage, this does not solve the problem because anyone can easily have multiple cellphone numbers. A person in cyber world can be an anonymous subject and take various actions that harm others, including stalking others. Stalking, done by the person behind an anonymous account is an annoying action, has not been regulated clearly in Indonesian. This paper is the result of a normative juridical study. Result of this research is: criminal law regulation system in Indonesia regulated cyberstalking as long as the action consist of delivery of illegal contents such as threats, obscene content and insults. Further regulation is still needed, especially regarding law enforcement mechanisms for perpetrators that are difficult to reach due to the use of the anonymous account.